Impact of Supply Chain Practices on Organizational Performance with Moderating Effect of Supply Chain Performance in Indian Health Care Industry - Bhavana Mathur; Sumit Gupta; Makhan Lal Meena; Govind Sharan Dangayach (International Journal of Supply Chain Management, 2018)
Supply chain practices play an important role in healthcare Organizational Performance. Organizational performance, from the perspective of Indian healthcare industry, is concerned with producing and delivering high-quality service at a reasonable cost. On the other hand, is concerned with how stakeholders are observing their organizations in terms of customer satisfaction, return on investment. The aim of this study was to assess the hypothesized relationship between Supply chain practices along with supply chain performance and organizational performance among Indian healthcare industry. The study was conducted by utilizing structured, self-administered questionnaires and collected data was analyzed by using SPSS. Study revealed that there is a positive significant relationship between supply chain practices and supply chain performance is affecting the organizational performance of the Indian healthcare industry.